IMPROVING DATA SECURITY IN CLOUD REPOSITORY: FUTURE CHALLENGES IN ELECTRONIC RECORDS MANAGEMENT - Achmad Fachmi; Wira Sakinatun Najahah; Adista Nurfitria; Taufik Asmiyanto; M. Hanif Inamullah (JEVIEF : Jurnal Vokasi FISIP Universitas Lampung, 2026)
The use of cloud-based storage for electronic archive on one hand can increase transparency of the use of data, but on the other hand it raises challenges in maintaining authenticity, accuracy, and reliability of the data, which is the basis of user trust in the managed data. This article focuses on the efforts to establish data security policies carried out by organizations as part of the process of utilizing, storing, and managing cloud-based data. This article also aims to provide recommendations for future policies, especially on security and trust issues in using cloud as data repository. Method used in this study is a literature review with aim to develop critical thinking on data security aspects in cloud storage systems and explain security and trust issues of data stored in the cloud. In addition, litmaps.co is used to map the distribution of related articles as supporting literature. The finding of this study shows that the problem of data breaches ranks at the top in relation to the security of data stored in the cloud, so the security challenge does not lie with the system or cloud provider, but in the mastery of policies and technology. Therefore, improving data security in cloud storage and cloud data management can be done by choosing the suitable type of cloud, modeling data security architecture according to possible security threats and applying data management principles such as respect des fonds and provenance. Governments can play a role in improving data security by providing privacy policies and cloud data management as well as facilitating the development of blockchain technology to improve data security